KECERDASAN ADVERSITY DAN KECEMASAN MENJELANG BEBAS PADA ANAK BINAAN - Isna Farihatul Husna; Zun Azizul Hakim (Institut Agama Islam Negeri (IAIN) Manado, 2023)
ABSTRACTThe aim of this research is to determine, whether there is a relationship between adversity intelligence and pre-release anxiety among juvenile inmates in class I Blitar juvenile prison or not. Participants in this study are juvenile inmates who will be released within a period of 6 months, with a total of 34 participants. The measuring tool used in this research is the Adversity Response Profile (ARP) scale consisting of 37 items (α = 0.976), the anxiety scale was developed based on the definition or theory expressed by Nolen, consisting of 39 items (α=0.972). The data analysis technique used to prove the hypothesis in this research is the Pearson product-moment correlation technique. The research results indicate that there is a relationship between adversity intelligence and pre-release anxiety in juvenile inmates with a negative correlation (r = 0.724, n = 34, p <0.001). Based on the research findings, it can be interpreted that the higher the level of adversity intelligence, the lower the level of anxiety experienced, and vice versa, if the level of adversity intelligence is low, the level of anxiety will increase.Keywords: adversity intelligence, anxiety, juvenile inmates ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara kecerdasan adversity dengan kecemasan menjelang bebas pada anak binaan di Lembaga Pembinaan Khusus Anak (LPKA) kelas I Blitar. Partisipan pada penelitian ini adalah anak binaan yang menjelang bebas dalam rentang waktu 6 bulan dengan jumlah partisipan 34 anak binaan. Alat ukur yang digunakan pada penelitian ini adalah skala Adversity Response Profile (ARP) yang berjumlah 37 aitem (α= 0,976), skala kecemasan disusun berdasarkan definisi atau teori yang diungkapkan oleh Nolen yang berjumlah 39 aitem (α= 0,972). Teknik analisis data yang digunakan untuk membuktikan hipotesis pada penelitian ini adalah teknik korelasi product moment dari Pearson. Hasil penelitian menunjukkan bahwa terdapat hubungan antara kecerdasan adversity dengan kecemasan menjelang bebas pada anak binaan dengan korelasi negatif (r = -0,724, n = 34, p < 0,001). Berdasarkan hasil penelitian tersebut dapat diartikan bahwa semakin tinggi tingkat kecerdasan adversity maka semakin rendah tingkat kecemasan yang dialami, begitu pula sebaliknya jika keserdasan adversity rendah maka tingkat kecemasan akan semakin tinggi. Kata Kunci: anak binaan, kecemasan, kecerdasan adversity